Effectiveness of Emission Control Policies: Bibliometric Insights Across Economic Contexts - Livia Ayu Intan Lestari; Aida Roestiyadi; Cyntia Widya Ariastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Global climate change has prompted analysis of emission control policies, including carbon trading mechanisms and carbon taxes, to achieve a low-carbon economy. This study utilizes a bibliometric approach (2020–2025) with the Scopus database, which is processed using the RStudio application with Bibliometrix and Biblioshiny analysis and also uses the VOSviewer application, to identify publication trends and the effectiveness of emissions policies in different economic contexts, such as G20 countries or developed countries with developing countries. Thematic analysis results show dominant topics such as emissions trading, carbon capture, renewable energy, and a focus on economic development and technological innovation. The reviewed literature confirms that higher carbon tax rates are more effective in reducing emissions in G20 countries, while in developing countries, the implementation of a combination of strict carbon taxes and emissions trading mechanisms can promote substantial decarbonization. Overall, this bibliometric study confirms the growing research interest in green economy solutions and supports the urgency of adaptive, evidence-based emissions policies in various economic contexts.